EFFECT OF DURATION BREASTFEEDING TOWARD def-t INDEX OF 2-3 YEARS OLD CHILD IN POSYANDU PUSKESMAS - Ummu Hanifah Amri; Harfindo Nismal (Andalas Dental Journal, 2016)
There are main factors that play role in the occurrence of caries, those are host factors, microorganism, substrate, and time. If one factor is not there then caries does not occur. Breastfeeding is fat emulsion in a solution of protein, lactose, and organic salt that are secreted by the breast. Breastfeeding contains nutrients that can inhibit caries occurrence. The aim of this study is to determine effect of duration breastfeeding toward def-t Index of 2-3 years old child in Posyandu Puskesmas Andalas. This study design is an observational with cross sectional design. The total sample were 68 of 2-3 years old children in Posyandu Puskesmas Andalas. The analysis effect of duration breastfeeding toward def-t Index is Chi Square’s Test. This study shows that there are significant effect (p<0,05) between duration breastfeeding toward def-t Index of 2-3 Years Old Child. def-t Index the moderate category for ≥6 months breastfeeding and def-t index the high category for <6 months breastfeeding.There is effect duration breastfeeding toward def-t Index of 2-3 years old. Key words : Breastfeeding, def-t Index, caries